A Novel Preparation of Nano-sized Hexagonal Mg(OH)2. (2015) - Chen, Yongbin; Zhou, Tao; Fang, Huaxiong; Li, Simin; Yao, Yuting; He, Yang
Abstract: Nano-sized dispersive hexagonal magnesium hydroxide (Mg(OH)2 ) was prepared by an ammonia-hydrothermal method. To improve the crystalline and dispersivity of magnesium hydroxide, citric acid was introduced into the reaction system at ammonia precipitation process and monoethanolamine (MEA) was introduced at hydrothermal process, respectively. In this study, the optimal parameters of nano-sized Mg(OH)2 preparation were obtained. The as-prepared Mg(OH)2 was characterized by SEM, XRD, TGA and etc. The results showed that the sample was hexagonal plates and had the mean diameter of 246 nm.